2016
DOI: 10.25077/jka.v5i2.523
|View full text |Cite
|
Sign up to set email alerts
|

Faktor Risiko yang Berhubungan dengan Kejadian Pneumonia pada Balita di Kelurahan Air Tawar Barat Padang

Abstract: AbstrakAda beberapa faktor risiko yang meningkatkan angka kejadian pneumonia di negara berkembang yaitu: kurangnya pemberian Air Susu Ibu (ASI) eksklusif, gizi buruk, polusi udara dalam ruangan, Bayi Berat Lahir Rendah (BBLR) dan kurangnya imunisasi campak. Tujuan penelitian ini adalah menentukan faktor risiko yang berhubungan dengan kejadian pneumonia pada balita di Kelurahan Air Tawar Barat, Kota Padang. Penelitian ini menggunakan desain case control study, sampel terdiri dari 27 case dan 27 control. Data di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
11
0
10

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 1 publication
6
11
0
10
Order By: Relevance
“…Exposure to cigarette smoke, especially at home and from family members, will increase the likelihood of ARI cases. This result was consistent with the study of Efni, Machmud, & Pertiwi (2016) explaining that the exposure to cigarette smoke in the home has a relationship with the incidence of pneumonia in infants.…”
Section: Discussionsupporting
confidence: 93%
“…Exposure to cigarette smoke, especially at home and from family members, will increase the likelihood of ARI cases. This result was consistent with the study of Efni, Machmud, & Pertiwi (2016) explaining that the exposure to cigarette smoke in the home has a relationship with the incidence of pneumonia in infants.…”
Section: Discussionsupporting
confidence: 93%
“…5 There were also studies in Padang and Kenya that said there was no significant correlation between birth weight and pneumonia in children. 5,6 Patria also said that most of researches had non significant result for birth weight. 7 Nevertheless, a study in Iran showed a significant result between decreased mortality from pneumonia with increasing birth weight.…”
Section: Discussionmentioning
confidence: 99%
“…Semakin besar imunisasi_DPT (Difteri,_Pertusis,_Tetanus) yang diberikan maka_semakin kecil pula_kejadian pneumonia_pada balita (34). Penelitian _yang _dilakukan di Kelurahan Air Tawar barat Kecamatan Padang Timur Kota Padang Sumatera Barat pada tahun 2013-2014 juga menunjukan dari 27 balita yang diteliti, 16 balita diantaranya tidak diimunisasi campak sedangkan 11 balita lainnya telah diimunisasi campak (35). Vaksin campak lebih_memiliki pengaruh langsung terhadap_pneumonia dibandingkan dengan_vaksin_pertusis.…”
Section: Analisis Korelasi Capaian Rumah Sehat Dan Imunisasi Dasar Leunclassified